Can the tumor-agnostic evaluation of MSI/MMR status be the common denominator for the immunotherapy treatment of patients with several solid tumors?. (February 2022) - Fanale, Daniele; Corsini, Lidia Rita; Scalia, Raimondo; Brando, Chiara; Cucinella, Alessandra; Madonia, Giorgio; Dimino, Alessandra; Filorizzo, Clarissa; Barraco, Nadia; Bono, Marco; Fiorino, Alessia; Magrin, Luigi; et al.
Highlights: dMMR/MSI showed important therapeutic and prognostic implications in CRC patients. dMMR/MSI-H is a potential biomarker able to predict the immunotherapy response. The tumor-agnostic MSI-H/dMMR evaluation could have a significant clinical impact. Abstract: Alterations in short-repetitive DNA sequences, known as microsatellite instability (MSI), can reflect deficiencies in Mismatch Repair (MMR) system which represents a major player in DNA integrity maintenance. The incidence of MSI-H/dMMR has been shown to be variable depending on the tumor type. Several studies confirmed that dMMR/MSI status, although less frequent than PD-L1 expression, may better predict response to immune-checkpoint inhibitors (ICIs) in patients with solid tumors. In October 2016, the FDA granted pembrolizumab as breakthrough therapy for the treatment of non-CRC, MSI-H/dMMR tumors, providing, for the first time, a tumor-agnostic indication. In the next future, the tissue-agnostic evaluation of MSI-H/dMMR could become the common denominator for the immunotherapy treatment of patients with different advanced solid tumors, in order to select patient subgroups which may benefit from this therapy. In this Review we provided an overview of the main clinical studies describing the association between MSI-H/dMMR tumors and immunotherapy response.